(untitled) (Journal of Enam Medical College, 2012)
Background: Preeclampsia is the most common and major medical complication of pregnancy with a high incidence of maternal and foetal morbidity and mortality. During pregnancy abnormally increased lipid peroxidation and free radical formation as well as significantly decreased antioxidants production in maternal blood may lead to pathogenesis of preeclampsia. So, we designed this study as little information is known about lipid peroxidation and antioxidant level in preeclampsia. Objectives: To assess the serum malondialdehyde (MDA) level as a lipid peroxidation product and vitamin E (antioxidant) level in women with preeclampsia as well as in normal pregnancy and to compare the values. Materials and Methods: The study was conducted on 60 women aged from 25 to 35 years in the department of Biochemistry, Budi Kemuliaan Maternity Hospital (BKMH) in Jakarta during the period April to July 2004. Twenty were normal pregnant women and 20 were preeclamptic patients. For comparison age matched 20 apparently healthy nonpregnant women were included in the study. The study subjects were selected from outpatient department (OPD) of Obstetrics and Gynaecology of BKMH in Jakarta. Serum MDA (lipid peroxidation product) level was measured by thiobarbituric acid reactive substances assay (TBRAS) method and vitamin E was estimated spectroflurometrically. Data were analyzed by unpaired Students t test between the groups by using SPSS version 12. Results: The mean serum MDA levels were significantly higher in normal pregnancy and also in preeclampsia than that of nonpregnant control group women (p<0.001). Again the serum MDA levels were significantly higher in preeclampsia than that of normal pregnant women (p<0.001). The serum vitamin E levels were significantly lower in preeclampsia and also in normal pregnancy than that of nonpregnant control women (p<0.001). Moreover, the serum vitamin E levels were significantly lower in preeclampsia compared to that of normal pregnancy which was also statistically significant (p<0.001) Conclusion: As in preeclamptic group level of oxidation product is high and antioxidant level is low, it can be assumed that in preeclampsia, serum antioxidants are excessively utilized to counteract the cellular damage mediated by free radicals production and deficient antioxidants as well as increased lipid peroxidations may be the important factors in the pathogenesis of preeclampsia. DOI: http://dx.doi.org/10.3329/jemc.v1i2.11462 J Enam Med Col 2011; 1(2): 56-59